IMPLIKASI HUKUM PERMENDAG NO. 3 TAHUN 2024 TERHADAP BISNIS JASTIP BARANG IMPOR DI INDONESIA: Legal Implications of Minister of Trade Regulation No. 3 of 2024 on the Jastip Imported Goods Business in Indonesia - Kusumarini, Andria (Jurnal Globalisasi Hukum., 2024)
This study examines the legal implications of the Minister of Trade Regulation (PERMENDAG) No. 3 of 2024, which amends PERMENDAG No. 36 of 2023, on the consignment service business for imported goods in Indonesia. In response to the dynamics of globalization and digital economic growth, this regulation was revised to strengthen import management by raising international compliance standards. The analysis shows that PERMENDAG No. 3 of 2024 introduces more detailed and strict provisions regarding licenses and import procedures, aiming to ensure the security and quality of imported goods. This step is crucial for maintaining consumer trust and ensuring fairness in Indonesia's business environment. Based on these regulatory changes, it is recommended that consignment business operators enhance their understanding of and compliance with the new regulations, and strengthen cooperation with suppliers and logistics partners to meet existing standards. The conclusion of the study is that the new regulation affects the consignment service business by demanding higher compliance and more organized import processes. It is advised that consignment businesses enhance their understanding of the new regulations, strengthen cooperation with suppliers, and ensure adherence to updated procedures.